TERM LIMIT EFFECTS IN INDONESIA: LOCAL GOVERNMENT REVENUE VS. SPENDING - Muamarah, Hanik Susilawati (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: The term limit of local leaders creates a puzzle between the "lame-duck effect" (declining performance) and the "competence effect" (improved performance). This study contextualizes this dilemma within the Indonesian context, which has strong incentives for non-re-election, such as the formation of political dynasties. We investigate this puzzle by examining the relationship between term-limited leaders and two distinct fiscal policy areas: regulation-bound tax revenue and discretionary capital expenditure. Methods: A fixed-effects model was employed to analyze panel data from 438 regencies and municipalities from 2017 to 2023. Findings: In the high-discretion area of spending, term-limited leaders increase capital expenditure, supporting agency theory, which suggests that leaders seek reputational incentives by leaving behind physical legacy projects. In contrast, no significant effect was found in the low-discretion revenue area, indicating that institutional constraints neutralize both the lame-duck and competence effects. Our model did not find sufficient support for the moderating effect of the COVID-19 pandemic as an external shock. Conclusion: The effect of term limits depends on policy discretion. Leaders pursue reputational incentives in high-discretion areas (spending), whereas the effect is limited in low-discretion areas (revenue). Novelty/Originality of this article: This study contributes to public sector accounting research by examining the connection between political incentives and local government fiscal policy decisions, with a focus on how term-limited leaders utilize their discretion in capital expenditure, particularly within a developing country and pandemic context subject to agency constraints.